Cultivation of Microalgae Using Sewage and Organic Component Evaluation. Issue 9 (10th August 2016) - Inoue, Kenichiro; Uchida, Tsutomu
Abstract: Outdoor cultivation of microalgae was carried out in 20‐L tanks using sewage influent or effluent, at an actual sewage treatment plant. The microalgae could be cultured by supplying only sewage influent or effluent without additional microalgal stock or nutrient salts. Adding air and CO2 to the culture water promoted not only the cultivation of green algae but also the consumption of nitrogen. Increasing the hydraulic retention time also promoted consumption and cultivation. In particular, adding CO2 to the sewage influent achieved a 59‐fold increase in the cell number of specific Scenedesmus species useful as components for fuel. The microalgae culture progressed even in the autumn/winter. The major organic components eluted by n ‐hexane were fatty acids such as palmitic and 11‐hexadecenoic acid. The applicability of sewage culture microalgae as biofuel was demonstrated. Abstract : Outdoor cultivation of microalgae was carried out using sewage influent or effluent. The microalgae could be cultured by supplying only sewage without additional microalgal stock or nutrient salts. The higher heating values of microalgae cultivated with a hydraulic retention time of 10 days ranged from 18 to 20 kJ g −1, demonstrating the applicability of sewage culture microalgae as biofuel.